Monitoring Structural Adjustment at the Microeconomic Level - Biggs, Tyler (World Bank, Washington, DC, 2012)
This paper describes a methodology for collecting information to monitor reform programs at the microeconomic level. Since narrowing the focus makes the explanation of this methodology more tractable the paper restricts its attention to the industrial sector. A more comprehensive monitoring of adjustment would include other economic sectors, as well as social indicators, such as poverty alleviation. A rather standard reform package is also assumed, one that has been implemented in several African countries. Additionally, since adjustments to changes in incentives take time and may proceed at different rates at different points of time, the monitoring exercise is designed to collect data over a sufficiently long period of time to capture the continuing process of adjustment. The details of what might be done in the first three years of such an exercise are examined here.